Efficacy of vaccination during pregnancy in reducing the risk of SARS-CoV-2 infection in infants younger than 12 months. Puglia (Italy), 2021-23 - Cesare De Virgilio Suglia; Pasquale Stefanizzi; Giusy Graziano; Lorenza Moscara; Arianna Delle Fontane; Martina Minelli; Silvio Tafuri (Taylor & Francis Group, 2024)
This retrospective cohort study evaluated the effectiveness of maternal vaccination against COVID-19 in reducing the risk of SARS-CoV-2 infection in infants younger than 12 months. The study, conducted at the "Policlinico" University Hospital of Bari, included 3346 newborns and their mothers. The study explored the degree of protection offered by maternal vaccination depending on the timing, type, and trimester of vaccination, also taking into account the mother's history of infection. We compared the incidence rate of infection between children of vaccinated and unvaccinated mothers; the values were 10.2% and 18.1%, respectively, and the difference was statistically significant. The overall effectiveness of the vaccine against the infection was 45%. Further analysis revealed increasing efficacy as the doses of vaccine administered to the mother increased and in case of a previous history of maternal infection. Dual immune stimulation (vaccination and natural infection) was 83% effective in preventing infection among newborns. The multivariable models confirmed the protective effect of vaccination with all types of vaccines used. The analysis of infection's incidence in newborns revealed an interesting temporal trend, with increasing incidence with time, suggesting a possible correlation with the persistence of maternal antibodies or with the gradual weaning. The results on the protective capacity of vaccines are in line with the global literature. Strengths of study include sample size, robust methodology, and multivariate analyses. Institutions could intensify awareness campaigns to encourage both pregnant women and all those who would like to become pregnant to receive SARS-CoV-2 vaccination.